Taking a shower in Youth Hostels: risks and delights of heterogeneity - Christina Matzke; Damien Challet (University of Bonn, Bonn Graduate School of Economics (BGSE), 2008)
Tuning one's shower in some hotels may turn into a challenging coordination game with imperfect information. The temperature sensitivity increases with the number of agents, making the problem possibly unlearnable. Because there is in practice a finite number of possible tap positions, identical agents are unlikely to reach even approximately their favorite water temperature. Heterogeneity allows some agents to reach much better temperatures, at the cost of higher risk.
Keywords: C02; C61; C62; C63; D70; D83; 330; coordination; heterogeneity; adaptive learning; non-linear system; feedback; Spieltheorie; Unvollkommene Information; Nichtlineare Optimierung; Lernprozess; Koordination; Public Choice; Theorie